Numerical Analysis of Infill Plate Performance on Steel Plate Shear Wall (SPSW) - Yobelita, Naomi; Siswosukarto, Suprapto; Muslikh, Muslikh; Purba, Ronny (INERSIA lnformasi dan Ekspose Hasil Riset Teknik Sipil dan Arsitektur, 2023)
Steel Plate Shear Wall (SPSW) is one of the systems that can be used to minimize the effect of earthquakes on buildings. The main energy-absorbing element of the steel plate shear wall system is on the thin steel plate that are located on the center of the steel frame. This thin steel plate is called infill plates. This infill plate will later experience buckling and form a series of tension field action. This paper will prove that the infill plates in the steel plate shear wall system provides significant strength contribution in resisting lateral loads.The analysis was carried out by comparing the strength provided by steel plate shear wall system and simple beam-column steel frame system (without infill plate) with some aspect ratio variation (width per height). The material used for the infill plates was low yield strength (LYS) steel plate of 1.30 mm thick, while the column (vertical boundary element) used WF 400.200.8.12, and the beam (horizontal boundary element) used WF 350.175.7.11. The loading used a monotonic pushover loading of 2% drift (68.8 mm) for each specimen.The analysis result proved that the steel plate shear wall system (frame with infill plates) had significant strength advantage compared to the plateless frame system. The aspect ratio (L/h) on infill plates were also affects the strength of the entire system, where the greater the aspect ratio, the greater the strength. The strength value of the SPSW specimen at 2% drift loading on aspect ratio L/h = 1.00, 1.50, 2.00, 2.50 respectively was 614.95 kN, 634.88 kN, 646.69 kN, and 688.03 kN. Meanwhile, the strength increment percentage between steel plate shear wall systems compared to plateless frame systems in each aspect ratio was 21.67%, 32.39%, 42.48%, and 54.20%.